Adopt the THINK campaign to encourage responsible social media use. Issue 6 (19th September 2016) - Miles, David
Abstract : We live in a digital and technological age, and there are new ways to communicate without ever having to talk face to face to someone. It seems like just about every other day a new application is coming out for people to connect and communicate with others.